A fireproof wire and cable with high safety performance and preparation method thereof

By covering the sheath material with flame retardant, fireproof, waterproof and oilproof on the wires and cables, the problem of wires and cables being prone to large-scale fires in fires is solved, and the effect of the cables maintaining normal operation in the flames is achieved.

CN118755174BActive Publication Date: 2025-04-29河北顺成线缆有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410950688.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-15
Publication Date
2025-04-29
Estimated Expiration
2044-07-15

AI Technical Summary

Technical Problem

Existing wires and cables are prone to large-scale fires when fire occurs, and cannot maintain normal operation after combustion, which cannot meet the power supply needs of important places during fires.

Method used

It is made of a high-safety fire-resistant wire and cable. The sheath is made by reacting phosphorus oxychloride, melamine and 2,2,2-trifluoroethanol and other materials. It is made by combining nano silicon nitride powder and composite silane coupling agent and cross-linking and extrusion granulation through ultraviolet radiation. It has the effects of flame retardant and fireproof, waterproof and oil-proof, and stain-resistant self-cleaning.

Benefits of technology

The fire-resistant wire cable can still maintain normal operation when burned in the flame, with extremely high safety, extending its application surface and improving the durability and safety of the cable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004947155300000051
    Figure BDA0004947155300000051
  • Figure BDA0004947155300000052
    Figure BDA0004947155300000052
  • Figure BDA0004947155300000061
    Figure BDA0004947155300000061
Patent Text Reader

Abstract

The present invention proposes a fireproof wire and cable with high safety performance and a preparation method thereof, and belongs to the technical field of wire and cable. It includes a copper wire and a sheath material coated on the surface of the copper wire. The preparation method of the sheath material is as follows: after phosphorus oxychloride and melamine react, react with 2,2,2-trifluoroethanol to obtain an intermediate 2, react with a nano-nano powder modified by a composite silane coupling agent with an amino group and a double bond, add it to a polyethylene resin together with an initiator, cross-link by ultraviolet radiation, extrude and granulate, and obtain the sheath material. The sheath material prepared by the present invention has the effects of flame retardancy, fire prevention, waterproof and oil proof, stain resistance and self-cleaning, short circuit prevention, leakage prevention, and aging resistance. The fireproof wire and cable obtained by coating it on the surface of the copper wire has extremely high safety. The cable can still maintain normal operation when it is burned in the flame, thereby greatly expanding its application surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electric wires and cables, and in particular to a fireproof electric wire and cable with high safety performance and a preparation method thereof. Background Art

[0002] With the development of society and the advancement of science and technology, many large-scale group companies, high-rise buildings, public entertainment venues, subways and underground streets have emerged, and their electricity consumption has increased day by day, and the variety and amount of wires and cables have also increased accordingly. Wires and cables can transmit and distribute electrical energy and transmit information, but they are also important factors that cause fires. Cable insulation and sheath materials are mostly flammable polyethylene, polyvinyl chloride, cross-linked polyolefins, ethylene propylene rubber, etc., which are easily ignited by short circuits, overheating, and exposure to other fire sources during use. The flame will spread rapidly along the outer material to the surrounding facilities and buildings during burning. Relevant data show that the flame can spread at a speed of up to 20m / min along the vertical line direction of the cable, accompanied by the formation of a large amount of molten drippings and toxic gases, causing immeasurable economic losses and casualties. At the same time, ordinary cables cannot be powered on once they are burned in an actual fire, but in many important occasions, when a fire occurs, personnel evacuation, channel lighting, fire alarm devices, automatic fire fighting facilities and other emergency equipment require that the cable can be powered on normally within the specified time when a fire occurs. Therefore, high-security fire-resistant cables came into being.

[0003] Fireproof cables refer to wires and cables that can maintain normal operation even when burned in flames under specified conditions and time. Currently, many fireproof cables use mica tape wrapped around the cable conductor, but this method cannot effectively and reliably ensure the normal operation of the cable in the event of a fire. Summary of the invention

[0004] The purpose of the present invention is to provide a fireproof wire and cable with high safety performance and a preparation method thereof. The prepared sheath material has the effects of flame retardancy and fireproofing, waterproof and oil-proofing, stain-resistant and self-cleaning, short-circuit-proofing, leakage-proofing and aging-resistant. The fireproof wire and cable prepared by coating the sheath material on the surface of the copper wire has extremely high safety. The cable can still maintain normal operation when burned in the flame, thereby greatly expanding its application.

[0005] The technical solution of the present invention is achieved in this way:

[0006] The invention provides a fireproof wire and cable with high safety performance, comprising a copper wire and a sheath material coated on the surface of the copper wire. The preparation method of the sheath material is as follows: phosphorus oxychloride and melamine are reacted, and then reacted with 2,2,2-trifluoroethanol to obtain an intermediate 2, and reacted with nanometer powder modified by a composite silane coupling agent with amino groups and double bonds, and added together with an initiator into a polyethylene resin, cross-linked by ultraviolet radiation, and extruded and granulated to obtain the sheath material.

[0007] As a further improvement of the present invention, the preparation method of the sheath material is specifically as follows:

[0008] S1. Under inert gas protection, phosphorus oxychloride was dissolved in dichloroethane, a dichloroethane solution of melamine was added dropwise, the reaction was heated with stirring, cooled to room temperature, filtered, washed, and dried to obtain intermediate 1;

[0009] S2. The intermediate 1 was added to acetonitrile, and under the protection of an inert gas, aluminum chloride and 2,2,2-trifluoroethanol were added, the reaction was heated and stirred, filtered, and the solvent was removed under reduced pressure to obtain an intermediate 2;

[0010] S3. The nano-silicon nitride powder is added to the silica sol, a composite silane coupling agent is added, the reaction is heated and stirred, centrifuged, washed, dried, and ball-milled to obtain a modified nano-powder;

[0011] S4. The modified nanopowder is added to acetonitrile, and under inert gas protection, intermediate 2 is added, the reaction is heated and stirred, centrifuged, washed, and dried to obtain a modifier;

[0012] S5. The polyethylene resin, the modifier and the initiator are mixed, cross-linked by ultraviolet radiation, and fed into a twin-screw extruder for melt blending and extrusion granulation to obtain a sheath material.

[0013] As a further improvement of the present invention, the molar ratio of phosphorus oxychloride to melamine in step S1 is 3-3.1:1, the temperature of the heating and stirring reaction is 50-60° C., and the time is 4-6 hours.

[0014] As a further improvement of the present invention, the molar ratio of the intermediate 1 and 2,2,2-trifluoroethanol in step S2 is 1-1.1:1, the amount of aluminum chloride added is 0.01-0.02wt% of the total mass of the system, and the temperature of the heating and stirring reaction is 70-80°C and the time is 3-5h.

[0015] As a further improvement of the present invention, the preparation method of the silica sol in step S3 is as follows: adding alkyl orthosilicate to ethanol, adding ammonia water, stirring and hydrolyzing to obtain silica sol; the alkyl orthosilicate is methyl orthosilicate or ethyl orthosilicate, the mass ratio of the alkyl orthosilicate, ethanol, and ammonia water is 10-15:80-100:7-12, the concentration of the ammonia water is 25-28wt%, the stirring and hydrolysis time is 10-12h, and the average particle size of the nano silicon nitride powder is The nano silicon nitride powder has a thickness of 20-40 nm, the mass ratio of the nano silicon nitride powder, the silica sol and the composite silane coupling agent is 10-15:100:5-7, the composite silane coupling agent is selected from at least two of KH550, KH602, KH792 and KH570, preferably, it is a mixture of KH792 and KH570, the mass ratio is 12-15:4-7, the temperature of the heating and stirring reaction is 45-55°C, the time is 2-3h, and the time of the ball milling is 1-2h.

[0016] As a further improvement of the present invention, in step S4, the mass ratio of the modified nano powder to the intermediate 2 is 15-20:2-3, the temperature of the heating and stirring reaction is 70-80° C., and the time is 5-7 h.

[0017] As a further improvement of the present invention, the mass ratio of the polyethylene resin, the modifier and the initiator in step S5 is 100:7-10:0.1-0.2, the initiator is a mixture of azobisisobutyronitrile and 1-hydroxycyclohexylphenyl ketone in a mass ratio of 1:2-4, the cross-linking reaction time is 1-2h, the melt blending temperature is 120-140°C, and the time is 1-2h.

[0018] The present invention further protects a fireproof wire and cable with high safety performance produced by the above-mentioned preparation method.

[0019] The present invention further protects the application of the above-mentioned fireproof wire and cable with high safety performance in fireproof buildings.

[0020] The present invention further protects a sheath material, the preparation method of which comprises the following steps:

[0021] S1. Under the protection of inert gas, 3-3.1 molar equivalents of phosphorus oxychloride are dissolved in dichloroethane, 1 molar equivalent of melamine in dichloroethane is added dropwise, heated to 50-60 ° C, stirred for 4-6 hours, cooled to room temperature, filtered, washed, and dried to obtain intermediate 1;

[0022] S2. 1-1.1 molar equivalents of intermediate 1 are added to acetonitrile, and under inert gas protection, aluminum chloride and 1 molar equivalent of 2,2,2-trifluoroethanol are added, wherein the amount of aluminum chloride added is 0.01-0.02wt% of the total mass of the system, heated to 70-80° C., stirred for 3-5h, filtered, and the solvent was removed under reduced pressure to obtain intermediate 2;

[0023] S3. 10-15 parts by weight of nano silicon nitride powder is added to 100 parts by weight of silica sol, 5-7 parts by weight of a composite silane coupling agent is added, heated to 45-55 ° C, stirred for 2-3h, centrifuged, washed, dried, and ball-milled for 1-2h to obtain a modified nanopowder;

[0024] The composite silane coupling agent is a mixture of KH792 and KH570, with a mass ratio of 12-15:4-7;

[0025] The preparation method of the silica sol is as follows: 10-15 parts by weight of alkyl orthosilicate is added to 80-100 parts by weight of ethanol, 7-12 parts by weight of 25-28 wt% ammonia water is added, and the mixture is stirred and hydrolyzed for 10-12 hours to obtain the silica sol;

[0026] S4. 15-20 parts by weight of the modified nanopowder is added to acetonitrile, under inert gas protection, 2-3 parts by weight of intermediate 2 is added, heated to 70-80 ° C, stirred for 5-7h, centrifuged, washed, and dried to obtain a modifier;

[0027] S5. 100 parts by weight of polyethylene resin, 7-10 parts by weight of modifier and 0.1-0.2 parts by weight of initiator are mixed, cross-linked by ultraviolet radiation for 1-2h, fed into a twin-screw extruder, melt blended at 120-140 ° C for 1-2h, extruded and granulated to obtain a sheath material;

[0028] The initiator is a mixture of azobisisobutyronitrile and 1-hydroxycyclohexylphenyl ketone, with a mass ratio of 1:2-4.

[0029] The present invention has the following beneficial effects:

[0030] In the present invention, phosphorus oxychloride and melamine are reacted to obtain intermediate 1. Since melamine is in a small amount, intermediate 1 with the following structural formula is obtained. The synthesis route is as follows:

[0031]

[0032] Intermediate 1 reacts with 2,2,2-trifluoroethanol under the action of aluminum chloride as a catalyst to obtain intermediate 2. Since the amounts of the two substances are equivalent, the synthesis route is as follows:

[0033]

[0034] Nano silicon nitride has good fireproof and fire-resistant effects. It is added to the silica sol obtained after hydrolysis to form ceramic silica gel. After being modified by a composite silane coupling agent, the composite silane coupling agent includes a silane coupling agent with an amino group and a silane coupling agent with a double bond. The surface of the modified nano powder has an amino group and a double bond. It reacts with the intermediate 2 to obtain a modifier. The route is as follows:

[0035]

[0036] In summary, the modifier (PN-Si halogen-free flame retardant) prepared by the present invention not only has a good flame retardant and fireproof effect, but also can catalyze the matrix to form a continuous and dense carbon layer to prevent the transfer of heat and oxygen to the matrix. At the same time, it will also release non-combustible gas during the combustion process, increase the height of the carbon layer, and dilute the concentration of oxygen, thereby achieving the effect of preventing combustion. At the same time, it has abundant double bond groups, including C=N and P=O bonds. These chromophores with absorption wavelengths less than 400nm are used to convert the absorbed ultraviolet rays into heat energy or harmless low energy, thereby achieving the ability of ultraviolet shielding and reducing the influence of ultraviolet rays on the material matrix, so that the prepared sheath material has good anti-ultraviolet aging performance and prolongs its service life. The multiple CF groups it contains can migrate to the surface layer of the material, significantly reducing the surface energy of the material, so that the prepared material has good waterproof, oil-proof, dirt-resistant and self-cleaning effects. In addition, the modifier also contains double bonds, which can be cross-linked with unreacted double bonds in polyethylene under the action of the initiator, thereby improving the compatibility and dispersibility of the modifier, and further improving the strength and mechanical properties of the polyethylene material. At the same time, the material has good insulation properties and is good in preventing short circuits and leakage, making it widely used in industry.

[0037] The sheath material prepared by the present invention has the effects of flame retardancy, fire resistance, water and oil resistance, stain resistance and self-cleaning, short circuit prevention, leakage prevention and aging resistance. The fireproof wire and cable prepared by coating the sheath material on the surface of the copper wire has extremely high safety. The cable can still maintain normal operation when burned in the flame, thereby greatly expanding its application. DETAILED DESCRIPTION

[0038] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] The polyethylene resin is PE: M2320 (MFR is 20.0 g / min), purchased from Sinopec Zhenhai Refining and Chemical Company. The average particle size of nano silicon nitride powder is 15±5 nm, purchased from Nangong Xindun Alloy Welding Material Spraying Co., Ltd.

[0040] Example 1

[0041] A fireproof wire and cable with high safety performance, characterized in that it comprises a copper wire and a sheath material coated on the surface of the copper wire. The preparation method of the sheath material comprises the following steps:

[0042] S1. Under nitrogen protection, 0.3 mol phosphorus oxychloride was dissolved in 200 mL dichloroethane, 50 mL 0.1 mol melamine dichloroethane solution was added dropwise, heated to 50 ° C, stirred for 4 hours, cooled to room temperature, filtered, washed, and dried to obtain intermediate 1; ESI-MS calculated value: C3H3Cl6N6O3P3 (M+H) + 474.76, measured value: 474.8, yield is 77%. NMR results: 1 HNMR (300MHz, CDCl3) δ4.05 (br, 3H).

[0043] S2. Add 0.1 mol of intermediate 1 to 200 mL of acetonitrile, add aluminum chloride and 0.1 mol of 2,2,2-trifluoroethanol under nitrogen protection, the amount of aluminum chloride added is 0.01 wt% of the total mass of the system, heat to 70°C, stir to react for 3 hours, filter, and remove the solvent under reduced pressure to obtain intermediate 2; ESI-MS calculated value: C9H9Cl3F9N6O6P3(M+H)+435.33, measured value: 435.3, yield is 90%. NMR results: 1HNMR (300 MHz, CDCl3) δ4.12 (s, 6H), 4.1 (br, 3H).

[0044] S3. 10 g of nano silicon nitride powder was added to 100 g of silica sol, 5 g of composite silane coupling agent was added, heated to 45 ° C, stirred for 2 h, centrifuged, washed, dried, and ball milled for 1 h to obtain modified nanopowder;

[0045] The composite silane coupling agent is a mixture of KH792 and KH570, with a mass ratio of 12:4;

[0046] The preparation method of the silica sol is as follows: 10g of methyl orthosilicate is added to 80g of ethanol, and 7g of 25wt% ammonia water is added, and the mixture is stirred and hydrolyzed for 10h to obtain the silica sol;

[0047] S4. 15 g of the modified nanopowder was added to 200 mL of acetonitrile, and 2 g of intermediate 2 was added under nitrogen protection, heated to 70 ° C, stirred for 5 h, centrifuged, washed, and dried to obtain a modifier;

[0048] S5. 100 g of polyethylene resin, 7 g of modifier and 0.1 g of initiator were mixed, cross-linked by UV irradiation for 1 h, fed into a twin-screw extruder, melt blended at 120 ° C for 1 h, extruded and granulated to obtain a sheath material;

[0049] The initiator is a mixture of azobisisobutyronitrile and 1-hydroxycyclohexylphenyl ketone, with a mass ratio of 1:2.

[0050] Example 2

[0051] A fireproof wire and cable with high safety performance, characterized in that it comprises a copper wire and a sheath material coated on the surface of the copper wire. The preparation method of the sheath material comprises the following steps:

[0052] S1. Under nitrogen protection, 0.31 mol of phosphorus oxychloride was dissolved in 200 mL of dichloroethane, 50 mL of 0.1 mol of melamine in dichloroethane was added dropwise, heated to 60 ° C, stirred for 6 hours, cooled to room temperature, filtered, washed, and dried to obtain intermediate 1;

[0053] S2. 0.11 mol of intermediate 1 was added to 200 mL of acetonitrile, and under nitrogen protection, aluminum chloride and 0.1 mol of 2,2,2-trifluoroethanol were added, wherein the amount of aluminum chloride added was 0.02 wt% of the total mass of the system, and the mixture was heated to 80 ° C., stirred for 5 h, filtered, and the solvent was removed under reduced pressure to obtain intermediate 2;

[0054] S3. 15 g of nano silicon nitride powder was added to 100 g of silica sol, 7 g of composite silane coupling agent was added, heated to 55 ° C, stirred for 3 h, centrifuged, washed, dried, and ball milled for 2 h to obtain modified nanopowder;

[0055] The composite silane coupling agent is a mixture of KH792 and KH570, with a mass ratio of 15:7;

[0056] The preparation method of the silica sol is as follows: 15g of ethyl orthosilicate is added to 100g of ethanol, 12g of 28wt% ammonia water is added, and the mixture is stirred and hydrolyzed for 12h to obtain the silica sol;

[0057] S4. 20 g of the modified nanopowder was added to 200 mL of acetonitrile, and 3 g of intermediate 2 was added under nitrogen protection, heated to 80 ° C, stirred for 7 h, centrifuged, washed, and dried to obtain a modifier;

[0058] S5. 100 g of polyethylene resin, 10 g of modifier and 0.2 g of initiator were mixed, cross-linked by UV irradiation for 2 h, fed into a twin-screw extruder, melt blended at 140 ° C for 2 h, extruded and granulated to obtain a sheath material;

[0059] The initiator is a mixture of azobisisobutyronitrile and 1-hydroxycyclohexylphenyl ketone, with a mass ratio of 1:4.

[0060] Example 3

[0061] A fireproof wire and cable with high safety performance, characterized in that it comprises a copper wire and a sheath material coated on the surface of the copper wire. The preparation method of the sheath material comprises the following steps:

[0062] S1. Under nitrogen protection, 0.305 mol of phosphorus oxychloride was dissolved in 200 mL of dichloroethane, 50 mL of 0.1 mol of melamine in dichloroethane was added dropwise, heated to 55 ° C, stirred for 5 h, cooled to room temperature, filtered, washed, and dried to obtain intermediate 1;

[0063] S2. 0.105 mol of intermediate 1 was added to 200 mL of acetonitrile, and under nitrogen protection, aluminum chloride and 0.1 mol of 2,2,2-trifluoroethanol were added, wherein the amount of aluminum chloride added was 0.015 wt% of the total mass of the system, and the mixture was heated to 75 ° C., stirred for 4 h, filtered, and the solvent was removed under reduced pressure to obtain intermediate 2;

[0064] S3. 12 g of nano silicon nitride powder was added to 100 g of silica sol, 6 g of composite silane coupling agent was added, heated to 50 ° C, stirred for 2.5 h, centrifuged, washed, dried, and ball milled for 1.5 h to obtain modified nanopowder;

[0065] The composite silane coupling agent is a mixture of KH792 and KH570, with a mass ratio of 13:5;

[0066] The preparation method of the silica sol is as follows: 12g of tetraethyl orthosilicate is added to 90g of ethanol, 10g of 27wt% ammonia water is added, and the mixture is stirred and hydrolyzed for 11h to obtain the silica sol;

[0067] S4. 17 g of the modified nanopowder was added to 200 mL of acetonitrile, and 2.5 g of intermediate 2 was added under nitrogen protection, heated to 75 ° C, stirred for 6 h, centrifuged, washed, and dried to obtain a modifier;

[0068] S5. 100 g of polyethylene resin, 8.5 g of modifier and 0.15 g of initiator were mixed, cross-linked by UV irradiation for 1.5 h, fed into a twin-screw extruder, melt blended at 130 ° C for 1.5 h, extruded and granulated to obtain a sheath material;

[0069] The initiator is a mixture of azobisisobutyronitrile and 1-hydroxycyclohexylphenyl ketone, with a mass ratio of 1:3.

[0070] Comparative Example 1

[0071] Compared with Example 3, the difference is that step S1 is not performed.

[0072] The details are as follows:

[0073] S1. Add 0.105 mol of phosphorus oxychloride to 200 mL of acetonitrile, add aluminum chloride and 0.1 mol of 2,2,2-trifluoroethanol under nitrogen protection, wherein the amount of aluminum chloride added is 0.015 wt% of the total mass of the system, heat to 75 ° C, stir to react for 4 h, filter, and remove the solvent under reduced pressure to obtain an intermediate;

[0074] S2. 12 g of nano silicon nitride powder was added to 100 g of silica sol, 6 g of composite silane coupling agent was added, heated to 50 ° C, stirred for 2.5 h, centrifuged, washed, dried, and ball milled for 1.5 h to obtain modified nanopowder;

[0075] The composite silane coupling agent is a mixture of KH792 and KH570, with a mass ratio of 13:5;

[0076] The preparation method of the silica sol is as follows: 12g of tetraethyl orthosilicate is added to 90g of ethanol, 10g of 27wt% ammonia water is added, and the mixture is stirred and hydrolyzed for 11h to obtain the silica sol;

[0077] S3. 17 g of the modified nanopowder was added to 200 mL of acetonitrile, and 2.5 g of the intermediate was added under nitrogen protection, heated to 75 ° C, stirred for 6 h, centrifuged, washed, and dried to obtain a modifier;

[0078] S4. 100 g of polyethylene resin, 8.5 g of modifier and 0.15 g of initiator were mixed, cross-linked by UV irradiation for 1.5 h, fed into a twin-screw extruder, melt blended at 130 ° C for 1.5 h, extruded and granulated to obtain a sheath material;

[0079] The initiator is a mixture of azobisisobutyronitrile and 1-hydroxycyclohexylphenyl ketone, with a mass ratio of 1:3.

[0080] Comparative Example 2

[0081] Compared with Example 3, the difference is that no nano silicon nitride powder is added in step S3.

[0082] The details are as follows:

[0083] S1. Under nitrogen protection, 0.305 mol of phosphorus oxychloride was dissolved in 200 mL of dichloroethane, 50 mL of 0.1 mol of melamine in dichloroethane was added dropwise, heated to 55 ° C, stirred for 5 h, cooled to room temperature, filtered, washed, and dried to obtain intermediate 1;

[0084] S2. 0.105 mol of intermediate 1 was added to 200 mL of acetonitrile, and under nitrogen protection, aluminum chloride and 0.1 mol of 2,2,2-trifluoroethanol were added, wherein the amount of aluminum chloride added was 0.015 wt% of the total mass of the system, and the mixture was heated to 75 ° C., stirred for 4 h, filtered, and the solvent was removed under reduced pressure to obtain intermediate 2;

[0085] S3. 6 g of composite silane coupling agent was added to 100 g of silica sol, heated to 50 ° C, stirred for 2.5 h, centrifuged, washed, dried, and ball milled for 1.5 h to obtain modified nanopowder;

[0086] The composite silane coupling agent is a mixture of KH792 and KH570, with a mass ratio of 13:5;

[0087] The preparation method of the silica sol is as follows: 12g of tetraethyl orthosilicate is added to 90g of ethanol, 10g of 27wt% ammonia water is added, and the mixture is stirred and hydrolyzed for 11h to obtain the silica sol;

[0088] S4. 17 g of the modified nanopowder was added to 200 mL of acetonitrile, and 2.5 g of intermediate 2 was added under nitrogen protection, heated to 75 ° C, stirred for 6 h, centrifuged, washed, and dried to obtain a modifier;

[0089] S5. 100 g of polyethylene resin, 8.5 g of modifier and 0.15 g of initiator were mixed, cross-linked by UV irradiation for 1.5 h, fed into a twin-screw extruder, melt blended at 130 ° C for 1.5 h, extruded and granulated to obtain a sheath material;

[0090] The initiator is a mixture of azobisisobutyronitrile and 1-hydroxycyclohexylphenyl ketone, with a mass ratio of 1:3.

[0091] Comparative Example 3

[0092] Compared with Example 3, the difference is that steps S1, S2 and S4 are not performed.

[0093] The details are as follows:

[0094] S1. 12 g of nano silicon nitride powder was added to 100 g of silica sol, 6 g of composite silane coupling agent was added, heated to 50 ° C, stirred for 2.5 h, centrifuged, washed, dried, and ball milled for 1.5 h to obtain modified nanopowder;

[0095] The composite silane coupling agent is a mixture of KH792 and KH570, with a mass ratio of 13:5;

[0096] The preparation method of the silica sol is as follows: 12g of tetraethyl orthosilicate is added to 90g of ethanol, 10g of 27wt% ammonia water is added, and the mixture is stirred and hydrolyzed for 11h to obtain the silica sol;

[0097] S2. 100 g of polyethylene resin, 8.5 g of modified nanopowder and 0.15 g of initiator were mixed, cross-linked by UV irradiation for 1.5 h, fed into a twin-screw extruder, melt blended at 130 ° C for 1.5 h, extruded and granulated to obtain a sheath material;

[0098] The initiator is a mixture of azobisisobutyronitrile and 1-hydroxycyclohexylphenyl ketone, with a mass ratio of 1:3.

[0099] Test Example 1

[0100] The sheath materials prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to performance tests.

[0101] The tensile strength of the material is tested in accordance with GB / T 1040-2018 at a tensile speed of 50 mm / min; the notched impact strength is tested in accordance with GB / T 1043-2008.

[0102] UL-94 vertical combustion is tested according to GB / T 2408-2021, and the sample size is 100×1×0.2mm 3 .

[0103] Limiting Oxygen Index (LOI): Tested in accordance with GB / T 2406.2-2009, sample size is 80mm×10mm×4mm.

[0104] The volume resistivity is tested according to GB / T 1410-1989.

[0105] UV shielding performance: The UV shielding effect of the sample was evaluated by UV transmittance tested by Perkin Elmer's spectrophotometer. The sample test wavelength was 280nm and 320nm, and the sample thickness was about 0.15mm.

[0106] The results are shown in Table 1.

[0107] Table 1

[0108]

[0109] It can be seen from the above table that the sheath materials prepared in Examples 1-3 of the present invention have good mechanical strength, flame retardancy and hydrophobicity, good insulation and good UV shielding performance.

[0110] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A fireproof wire and cable with high safety performance, characterized in that: It includes a copper wire and a sheath material coated on the surface of the copper wire; The preparation method of the sheath material is specifically as follows: S1. Under the protection of inert gas, phosphorus oxychloride is dissolved in dichloroethane, a dichloroethane solution of melamine is added dropwise, the reaction is heated and stirred, cooled to room temperature, filtered, washed, and dried to obtain intermediate 1; the molar ratio of phosphorus oxychloride to melamine is 3-3.1:1; S2. The intermediate 1 is added to acetonitrile, and under the protection of an inert gas, aluminum chloride and 2,2,2-trifluoroethanol are added, the reaction is heated and stirred, filtered, and the solvent is removed under reduced pressure to obtain an intermediate 2; the molar ratio of the intermediate 1 to 2,2,2-trifluoroethanol is 1-1.1:1; S3. The nano-silicon nitride powder is added to the silica sol, a composite silane coupling agent having an amino group and a double bond is added, the reaction is heated and stirred, centrifuged, washed, dried, and ball-milled to obtain a modified nano-powder; the mass ratio of the nano-silicon nitride powder, the silica sol, and the composite silane coupling agent is 10-15:100:5-7; S4. The modified nanopowder is added to acetonitrile, and under inert gas protection, intermediate 2 is added, the reaction is heated and stirred, centrifuged, washed, and dried to obtain a modifier; the mass ratio of the modified nanopowder to the intermediate 2 is 15-20:2-3; S5. The polyethylene resin, the modifier and the initiator are mixed, cross-linked by ultraviolet radiation, and fed into a twin-screw extruder, melt-blended, extruded and granulated to obtain a sheath material; the mass ratio of the polyethylene resin, the modifier and the initiator is 100:7-10:0.1-0.

2.

2. The fireproof wire and cable with high safety performance according to claim 1, characterized in that: The temperature of the heating and stirring reaction in step S1 is 50-60° C. and the time is 4-6 hours.

3. The fireproof wire and cable with high safety performance according to claim 1, characterized in that: The amount of aluminum chloride added in step S2 is 0.01-0.02 wt% of the total mass of the system, the temperature of the heating and stirring reaction is 70-80° C., and the time is 3-5 h.

4. The fireproof wire and cable with high safety performance according to claim 1, characterized in that: The preparation method of the silica sol in step S3 is as follows: adding alkyl orthosilicate to ethanol, adding ammonia water, stirring and hydrolyzing to obtain silica sol; the alkyl orthosilicate is methyl orthosilicate or ethyl orthosilicate, the mass ratio of the alkyl orthosilicate, ethanol and ammonia water is 10-15:80-100:7-12, the concentration of the ammonia water is 25-28wt%, the stirring and hydrolysis time is 10-12h, the average particle size of the nano silicon nitride powder is 20-40nm, the composite silane coupling agent is selected from at least two of KH550, KH602, KH792 and KH570, the temperature of the heating and stirring reaction is 45-55°C, the time is 2-3h, and the ball milling time is 1-2h.

5. The fireproof wire and cable with high safety performance according to claim 4, characterized in that: The composite silane coupling agent is a mixture of KH792 and KH570, with a mass ratio of 12-15:4-7.

6. The fireproof wire and cable with high safety performance according to claim 1, characterized in that: The temperature of the heating and stirring reaction in step S4 is 70-80° C. and the time is 5-7 h.

7. The fireproof wire and cable with high safety performance according to claim 1, characterized in that: The initiator in step S5 is a mixture of azobisisobutyronitrile and 1-hydroxycyclohexyl phenyl ketone in a mass ratio of 1:2-4, the cross-linking reaction time is 1-2h, and the melt blending temperature is 120-140°C for 1-2h.

8. Use of the fireproof wire and cable with high safety performance as claimed in any one of claims 1 to 7 in fireproof buildings.

9. A sheath material, characterized in that: The preparation method comprises the following steps: S1. Under the protection of inert gas, 3-3.1 molar equivalents of phosphorus oxychloride are dissolved in dichloroethane, 1 molar equivalent of melamine in dichloroethane is added dropwise, heated to 50-60 ° C, stirred for 4-6 hours, cooled to room temperature, filtered, washed, and dried to obtain intermediate 1; S2. 1-1.1 molar equivalents of intermediate 1 are added to acetonitrile, and under inert gas protection, aluminum chloride and 1 molar equivalent of 2,2,2-trifluoroethanol are added, wherein the amount of aluminum chloride added is 0.01-0.02wt% of the total mass of the system, heated to 70-80° C., stirred for 3-5h, filtered, and the solvent was removed under reduced pressure to obtain intermediate 2; S3. 10-15 parts by weight of nano silicon nitride powder is added to 100 parts by weight of silica sol, 5-7 parts by weight of a composite silane coupling agent is added, heated to 45-55 ° C, stirred for 2-3h, centrifuged, washed, dried, and ball-milled for 1-2h to obtain a modified nanopowder; The composite silane coupling agent is a mixture of KH792 and KH570, with a mass ratio of 12-15:4-7; The preparation method of the silica sol is as follows: 10-15 parts by weight of alkyl orthosilicate is added to 80-100 parts by weight of ethanol, 7-12 parts by weight of 25-28 wt% ammonia water is added, and the mixture is stirred and hydrolyzed for 10-12 hours to obtain the silica sol; S4. 15-20 parts by weight of the modified nanopowder is added to acetonitrile, under inert gas protection, 2-3 parts by weight of intermediate 2 is added, heated to 70-80 ° C, stirred for 5-7h, centrifuged, washed, and dried to obtain a modifier; S5. 100 parts by weight of polyethylene resin, 7-10 parts by weight of modifier and 0.1-0.2 parts by weight of initiator are mixed, cross-linked by ultraviolet radiation for 1-2h, fed into a twin-screw extruder, melt blended at 120-140 ° C for 1-2h, extruded and granulated to obtain a sheath material; The initiator is a mixture of azobisisobutyronitrile and 1-hydroxycyclohexylphenyl ketone, with a mass ratio of 1:2-4.

Citation Information

Patent Citations

  • Nano-silicon dioxide and nano-silicon nitride composite material and preparation method thereof

    CN102931149A

  • Preparation method of modified cross-linked polyethylene insulated wire or cable

    CN111087672A